Hodnocení investic do energeticky úsporných opatření - Štěpánková, Kristýna (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce se zabývá energeticky úspornými opatřeními, prováděnými na budovách, způsobům financování investic do těchto opatření a metodami jejich ekonomického hodnocení. V teoretické části jsou popsány způsoby stanovení energetické náročnosti budov, typy energeticky úsporných opatření, možnosti financování a ekonomického hodnocení. V praktické části jsou popsána energeticky úsporná opatření, provedená na dvou panelových budovách a způsob jejich financování a ekonomické zhodnocení těchto investic.

Bachelor thesis deals with energy-saving measures implemented in buildings, financing of investments in these measures and methods of economic evaluation. The theoretical part describes how to determine the energy performance of buildings, types of energy-saving measures, funding opportunities and economic evaluation. The practical part describes the energy-saving measures, carried out on two prefabricated buildings and the method of financing and economic evaluation of these investments.
Evaluation of Investments in Energy Saving Measures
Keywords: Energeticky úsporná opatření; zateplování; energetická náročnost budov; metody hodnocení investic; dotační programy; úvěrové produkty.; Energy saving measures; thermal building insulation; energy performance requirements for buildings; methods of investment evaluation; subsidy programs; credit products.